Resonant O-Type Millimeter Wave Oscillator with the Inclined Focusing Field - Odarenko, E. N.; Shmat'ko, A. (SPIE, 1994)
This report investigates the influence of inclined focusing magnetic field (MF) on the starting current and efficiency of the resonant 0 -type oscillators (orotron, laddertron, resonant BWO). Analysis is carried out within two-dimensional model in which the finite transverse dimensions of the electron beam and interception of electrons by grating are taken into account. The numerical calculations results bear significant effect of the MF incline angle on the oscillators operation characteristics.
Keywords: tilted focusing field; O-type generator; nonlinear theory; two-dimensional model